2016
DOI: 10.1186/s12875-016-0440-0
|View full text |Cite
|
Sign up to set email alerts
|

The influence of gender and other patient characteristics on health care-seeking behaviour: a QUALICOPC study

Abstract: BackgroundCanadians’ health care-seeking behaviour for physical and mental health issues was examined using the international Quality and Cost of Primary Care (QUALICOPC) survey that was conducted in 2013 in Canada.MethodThis study used the cross-sectional Patient Experiences Survey collected from 7260 patients in 759 practices across 10 Canadian provinces as part of the QUALICOPC study. A Responsive Care Scale (RCS) was constructed to reflect the degree of health care-seeking behaviour across 11 health condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

49
510
17
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 742 publications
(589 citation statements)
references
References 17 publications
49
510
17
13
Order By: Relevance
“…However, participants in both studies were almost exclusively female (Biro, Veres-Balajti, and Kosa, 2016) (Twomey, 1991). This was perhaps because participation to engage in the peer support programme was voluntary with no other incentives, and females are more likely to associate with similar others (Szell and Thurner, 2013), and engage with help-seeking behaviours better than men (Thompson et al, 2016). Twomey (1991) agrees with the concept that "we like people and situations which provide reinforcement for us", however does not state that this theory is limited for females.…”
Section: Behaviour In Females Versus Malesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, participants in both studies were almost exclusively female (Biro, Veres-Balajti, and Kosa, 2016) (Twomey, 1991). This was perhaps because participation to engage in the peer support programme was voluntary with no other incentives, and females are more likely to associate with similar others (Szell and Thurner, 2013), and engage with help-seeking behaviours better than men (Thompson et al, 2016). Twomey (1991) agrees with the concept that "we like people and situations which provide reinforcement for us", however does not state that this theory is limited for females.…”
Section: Behaviour In Females Versus Malesmentioning
confidence: 99%
“…Thus, the intervention had a significant impact on mental wellbeing for those who engaged with it. Engagement in peer support is consistently higher in women, because are more likely to ask for help (Thompson et al, 2016). So, although peer support programmes may encourage students to seek support earlier, peer support intervention designs should be mindful that the methodology retains student engagement and appeals to both sexes.…”
Section: Different Agendas For Peer Supportmentioning
confidence: 99%
“…Several studies have indicated that females may be more biologically susceptible to chlamydia than males (18,19). Furthermore, they are also more likely to seek health care (19,20). Infections in females are frequently asymptomatic, and untreated infections can lead to serious complications and morbidity such as pelvic inflammation, ectopic pregnancies and infertility (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…33,35 The increased reliance on doctors as an important source of information for women also reflects trends in the literature that identify women as more likely to engage with health professionals. 36 Parents and health professionals were considered to be reliable due to their personal and professional relationships with participants. To potentiate this line of knowledge transfer, parents of adolescents and young adults should also receive osteoporosis information that focusses on long-term benefits of calcium and vitamin D intake.…”
Section: Discussionmentioning
confidence: 99%